Penerapan Arduino Mega 2560 pada Mesin Cetak Tiga Dimensi - Indrawan Bagus Pertiaz; Henny Leidiyana (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
The design and design of this three-dimensional printing machine concentrates on robotics enthusiasts who are very difficult to find prototype machine covers. The purpose of this research is to create a 3D printer machine design for users in order to shorten the time of making prototypes and be faster and more precise to make a container for robotic prototype needs. The supporting equipment used in the manufacture of the 3-dimensional printing machine in this research is Arduino Mega 2560, Ramps 1.4, A4988 Stepper Motor Driver, ESP8266 WIFI Module, HotEnd, HeatBed, Stepper Motor. The author conducted a test test of several different types of filaments. The research method used is an experimental quantitative method by providing input from the designed tool and then observing the results of the output. The stages of this research are analyzing the problem, defining problems and needs, designing, and measuring the level of accuracy and strength of the type of material used for printing between PLA (Polylactic Acid) filaments and ABS (Acrylonitrile Butadiene Styrene) filaments. From the two results, PLA requires a hotend temperature of 195 degrees Celsius with a heatbed temperature of 65 degrees Celsius, while ABS requires a hotend temperature of 250 degrees Celsius with a heatbed temperature of 110 degrees Celsius and it can be concluded that the strength level of ABS is stronger than PLA.